Feasibility Analysis of Empek- Empek end Tekwan in UMKM Poklahsar Pelangi Cakrawala Mandiri - Riani, Maria Ulfah (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Empek-empek and tekwan are West Sumatra specialties made from fish meat and seasoned with a special sauce which is very popular in South Kalimantan. This study aims to be able to analyze the size of business capital, profits, and analyze the feasibility of empek-empek and tekwan processing businesses in UMKM for POKLAHSAR Pelangi Cakrawala Mandiri. The research was conducted from July 2023 to August 2023. The UMKM POKLAHSAR Pelangi Cakrawala Mandiri has an address at Volunteer Gang Al-Aman, Loktabat Village, North Banjarbaru District, Banjarbaru City. The method used is observation by directly following the flow of the process of making empek-empek and tekwan starting from receiving raw materials to packaging the product and selling it in one month. The data analysis method used is the analysis of costs, revenues, profits, efficiency analysis and business risk analysis. The results of this study indicate that the processing of empek-empek and tekwan can provide great benefits. Sales of empek-empek and tekwan frozen food can provide promising business opportunities because the profits earned annually reach IDR 141.637.200,00. From the feasibility calculation of business analysis, R/C = 1,891 is obtained with BEP for empek-empek production = 1.785,67 and BEP for empek-empek prices = Rp. 35.823,6 while for BEP for tekwan production = 1.715,77 and BEP for tekwan prices = Rp. 11.915,1. Because the R/C is greater than 1 and the production BEP and the good price for empek-empak or tekwan is above the breakeven point, this frozen food business is feasible to do.